Beyond NAGPRA/Not NAGPRA. Issue 1 (March 2022) - Wheeler, Ryan; Arsenault, Jaime; Taylor, Marla
Institutions have been slow to respond to calls from Indigenous nations, organizations, and scholars to require free, prior, and informed consent before authorizing use of their cultural heritage materials in publications, exhibition, and research. In the United States, the Native American Graves Protection and Repatriation Act of 1990 fundamentally changed the relationship between museums, archaeologists, and Indigenous nations, requiring institutions to inventory their collections and consult with descendant communities on repatriation of specific Indigenous collections. In response, institutions and their personnel have come to view Indigenous collections as those subject to NAGPRA and those that are not—NAGPRA/Not NAGPRA. Many Indigenous nations, however, do not accept this demarcation, resulting in continued frustration and trauma for those descendant communities. This case study follows the evolving relationship between the White Earth Band of the Minnesota Chippewa Tribe and the Robert S. Peabody Institute of Archaeology. Beginning with repatriation, the relationship has expanded to consider how the museum and Indigenous nation can collaborate on the care and curation of cultural heritage materials that remain at the Peabody Institute. Most recently, White Earth and the Peabody have executed an MOU that governs how the museum will handle new acquisitions, found-in-collections materials, and donor offers. The relationship with the White Earth also has influenced how the Peabody Institute approaches its holdings of Indigenous cultural heritage materials more broadly, blurring the line between NAGPRA and Not NAGPRA collections. The Peabody Institute is working to revise its collections policy to require free, prior, and informed consent prior to use of Indigenous cultural heritage materials in publications, exhibitions, and research.